Thermal analysis of chitosan based networks - Neto, CGT; Giacometti, J. A.; Job, A. E.; Ferreira, F. C.; Fonseca, JLC; Pereira, M. R. (Elsevier B.V., 2005)
In this work two kinds of material were studied: chitosan cross-linked with glutaraldehyde and in a blend with PEO. The resulting products as well as chitosan and PEO raw materials, were analyzed by TG/DTG, DSC and DMTA to determinate the in?uence of cross-linking and PEO addition on thermal properties of the resulting materials. It was observed by thermogravimetry that the water-polymer interaction will be different for the cross-linked material compared to the blend, according to the specific site availability. The in?uence of such modifications (cross-linking and PEO addition), on chitosan thermal stability was also studied. The DSC results showed a good agreement with the TG/DTG results, reinforcing the interpretation given for TG/DTG results. DMTA results indicate that glass transition temperature is around 50 degrees C for the polymer under study. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: chitosan; thermal analysis; blends